Composite metal bipolar plate of fuel cell and preparation method of composite metal bipolar plate

By depositing conductive coatings on the surface of the metal matrix by electrophoretic deposition, and using the synergistic effect of polyaniline and other materials, the problem of insufficient mechanical strength and corrosion resistance of traditional bipolar plates is solved, and higher conductivity and service life are achieved.

CN119843336AActive Publication Date: 2025-04-18GUANGDONG SIDA HYDROGEN ENERGY TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510008303.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-18
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

Traditional graphite bipolar plates have low mechanical strength and high processing costs, while metal bipolar plates have poor corrosion resistance, which limits their application in fuel cells.

Method used

Electrophoretic deposition method is used to deposit conductive coatings on the surface of the metal matrix, and polyaniline, modified p-toluenesulfonic acid, multi-walled carbon nanotubes, reduced graphene oxide and chopped carbon fiber are added to the precursor solution to improve conductivity, mechanical strength and corrosion resistance through various interactions.

Benefits of technology

The corrosion resistance, mechanical strength, conductive properties and service life of the bipolar plate are significantly improved, the preparation process is simplified and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of fuel cells, in particular to a fuel cell composite metal bipolar plate and a preparation method thereof. Firstly, a metal matrix material is pretreated, and then a conductive coating is deposited on the surface of the metal matrix material; the preparation method of the conductive coating comprises the following steps: S1, preparing a precursor solution: dissolving polyaniline in N-methyl pyrrolidone, then adding modified p-toluenesulfonic acid, multi-walled carbon nanotubes, reduced graphene oxide and short carbon fibers, and carrying out ultrasonic treatment to obtain the precursor solution; s2, electrophoretic deposition: pouring the precursor solution into a deposition tank, inserting an electrode, and applying voltage for electrophoretic deposition; and S3, post-treatment: drying at 60-100 DEG C for 0.5-1.5 h, and curing at 120-160 DEG C for 2-4 h to obtain the product. According to the preparation method disclosed by the invention, the corrosion resistance, the mechanical strength, the conductivity and the service life of the bipolar plate are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a fuel cell composite metal bipolar plate and a preparation method thereof. Background Art

[0002] With the intensification of the energy crisis and the increasing severity of environmental pollution, fuel cells, as a clean and efficient energy conversion device, have received widespread attention. In fuel cells, bipolar plates, as one of the core components, undertake the important functions of separating reaction gases, collecting current, and distributing reaction gases. Although traditional graphite bipolar plates have good corrosion resistance, they have low mechanical strength and high processing costs; while metal bipolar plates have high mechanical strength and good conductivity, but their corrosion resistance is poor, which limits their application in fuel cells. In order to solve the above problems, researchers began to explore the surface modification technology of metal bipolar plates to improve their corrosion resistance and conductivity.

[0003] The Chinese invention patent with application number CN202311321161.6 discloses a surface treatment method for a fuel cell bipolar plate, comprising the following steps: providing a bipolar plate to be treated, placing the bipolar plate in a closed chamber; evacuating the chamber; filling the chamber with a diffusion gas, the diffusion gas comprising nitrogen, and at least one of an unsaturated organic gas and oxygen; heating the bipolar plate to a preset temperature for a gas diffusion reaction, and maintaining the temperature for a preset time to form a diffusion reaction layer extending inward from the surface of the bipolar plate inside the bipolar plate. The bipolar plate obtained by this invention patent has improved performance in a short period of time, but during long-term use, the stability and durability of the diffusion reaction layer are still insufficient and need to be further improved.

[0004] The Chinese invention with application number CN202410343289.0 discloses a gold plating method for a hydrogen fuel cell metal bipolar plate and a fuel cell, which realizes high conductivity and high durability of the metal bipolar plate coating by implementing a process of a primer layer-high tolerance buffer layer-gold plating layer on the metal bipolar plate. The present invention is obtained by implementing a coating method of a primer layer-high tolerance buffer layer-gold plating layer. By adding a high tolerance buffer layer, the secondary protection of the gold plating layer from the corrosion of the coating due to the infiltration of the corrosive liquid due to the dense defects in the local area can be increased, thereby achieving the purpose of increasing the durability of the entire coating. However, the multi-step electroplating process in the invention requires precise control of the thickness and electroplating conditions of each layer, which increases the complexity and difficulty of the production process and places high requirements on production equipment and operators. In the multi-layer electroplating process, it is difficult to ensure that each layer can achieve uniform thickness and performance distribution on the complex shape and surface of the bipolar plate. If there is uneven coating, it may affect the performance and life of the bipolar plate, and there may be insufficient interlayer bonding between the multilayer structure due to factors such as differences in thermal expansion coefficients and lattice matching. There may be a risk of coating peeling under long-term use or complex working conditions.

[0005] Therefore, further improving the conductivity of bipolar plates and enhancing their mechanical strength and corrosion resistance remain technical challenges. Summary of the invention

[0006] In order to solve the above problems, the purpose of the present invention is to provide a fuel cell composite metal bipolar plate and a preparation method thereof. The preparation method of the present invention significantly improves the corrosion resistance, mechanical strength, conductivity and service life of the bipolar plate. The bipolar plate is suitable for proton exchange membrane fuel cells and has broad application prospects.

[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0008] A method for preparing a composite metal bipolar plate for a fuel cell, first pre-treating a metal matrix material to remove surface impurities, and then depositing a conductive coating on the surface of the metal matrix by electrophoretic deposition;

[0009] The specific steps of electrophoretic deposition of the conductive coating are:

[0010] S1, preparation of precursor solution: dissolving polyaniline in N-methylpyrrolidone, stirring until completely dissolved, then adding modified p-toluenesulfonic acid as a dopant, continuing stirring for 20-40 minutes, then adding multi-walled carbon nanotubes and reduced graphene oxide, performing ultrasonic treatment, after uniform dispersion, adding chopped carbon fibers, continuing ultrasonic treatment, and obtaining a precursor solution;

[0011] S2, electrophoretic deposition: pour the precursor solution into the deposition tank, insert the electrode, apply voltage, and perform electrophoretic deposition on the surface of the metal substrate;

[0012] S3, post-treatment: drying at 60-100°C for 0.5-1.5h, curing at 120-160°C for 2-4h.

[0013] Preferably, in step S1, the weight volume ratio of the polyaniline to N-methylpyrrolidone is 0.5-1.5 g:40-60 ml, and the weight ratio of the polyaniline to modified p-toluenesulfonic acid, multi-walled carbon nanotubes, and reduced graphene oxide is 0.5-1.5:0.05-0.15:0.03-0.07:0.03-0.07.

[0014] Preferably, in step S2, stainless steel is used as the anode, the metal substrate is used as the cathode, and the electrode spacing is 2-4 cm; the electrophoretic deposition parameters are: voltage 20-40 V, deposition time 3-7 min, current density 1-3 mA / cm 2 .

[0015] In the precursor solution, polyaniline, modified p-toluenesulfonic acid, multi-walled carbon nanotubes, reduced graphene oxide and chopped carbon fibers jointly improve the electrical conductivity and other key properties such as mechanical strength, corrosion resistance and stability through multiple interactions and synergistic effects. Polyaniline is an important conductive polymer, and its conductivity can be significantly improved by doping with p-toluenesulfonic acid. As a dopant, p-toluenesulfonic acid can effectively dope quinone nitrogen atoms in polyaniline, thereby increasing its conductivity. Modified p-toluenesulfonic acid enters the polyaniline molecular chain through doping to form a charge transfer complex. This doping can increase the carrier concentration in the polyaniline molecular chain, thereby significantly improving the conductivity of polyaniline. Multi-walled carbon nanotubes and reduced graphene oxide have excellent conductivity and high specific surface area, and can form efficient electron transport channels in the polyaniline matrix. In addition, there is an electrostatic interaction between sulfonated polyaniline and multi-walled carbon nanotubes, which enhances the conjugation length and improves the electron mobility. The addition of multi-walled carbon nanotubes and reduced graphene oxide significantly increases the density of the conductive network, thereby improving the overall conductive performance. There are π-π conjugation and van der Waals forces between multi-walled carbon nanotubes and reduced graphene oxide and polyaniline. These interactions combine multi-walled carbon nanotubes, reduced graphene oxide and polyaniline to form a stable network structure, further enhancing the stability of the conductive network and promoting the rapid transmission of electrons, thereby improving the conductivity and mechanical properties of the overall material. The good conductivity of chopped carbon fibers makes it an effective conductive filler. The chopped carbon fibers form a three-dimensional conductive network in the conductive coating, providing additional electron transmission paths. At the same time, as a reinforcing material, carbon fibers are evenly dispersed in the conductive coating to form a physical support structure, which not only improves the mechanical strength of the coating, but also supports the entire conductive network through its three-dimensional structure, ensuring the continuity of the electron transmission path, and further improving the conductivity of the coating.

[0016] In addition, polyaniline itself has multiple functions such as shielding, passivation and corrosion inhibition. It can form a protective layer on the metal surface to prevent the penetration of corrosive media (such as water and oxygen). The doping mechanism of polyaniline enables it to maintain a stable chemical structure in a corrosive environment, thereby improving the durability of the coating. Modified p-toluenesulfonic acid can be used as a dopant to improve the water solubility and electrochemical properties of polyaniline. The anti-corrosion performance of polyaniline is further enhanced by doping, so that it is evenly dispersed in the coating and forms a dense protective layer. Multi-walled carbon nanotubes have excellent mechanical strength. Combined with polyaniline, they can increase the density and permeability of the coating, thereby improving its anti-corrosion ability. Reduced graphene oxide has a high specific surface area and good dispersibility, which can effectively isolate the contact between the corrosive medium and the metal substrate. The combination of reduced graphene oxide and polyaniline can significantly improve the barrier performance and anti-corrosion efficiency of the coating.

[0017] Preferably, in step S2, after the deposition is completed, the coating substrate is cleaned with N-methylpyrrolidone to remove undeposited particles and residues.

[0018] Preferably, the method for preparing the modified p-toluenesulfonic acid comprises the following steps:

[0019] Step 1, add p-toluenesulfonic acid to concentrated sulfuric acid and stir evenly; under ice bath conditions, add concentrated nitric acid dropwise for 30-45 min, maintain the reaction temperature at 0-5°C, and stir the reaction for 2.5-3.5 h; after the reaction, pour the reaction solution into ice water, let it stand for 30-60 min, and then filter to obtain a nitration product;

[0020] Step 2, dissolving the nitration product in anhydrous ethanol, adding hydrochloric acid and iron powder, heating to reflux for 3-5 hours, the heating temperature is 80-84° C., filtering to remove the iron powder, and removing the ethanol by vacuum distillation to obtain an amination product;

[0021] Step 3, dissolving the above-mentioned amination product in distilled water, stirring evenly, adding potassium permanganate, the reaction temperature is 60-70°C, reacting for 4-6 hours, adding sodium hydroxide solution to neutralize to a pH of 9-10, filtering to remove the precipitate, and then acidifying the filtrate with hydrochloric acid to a pH of 2-3 to precipitate the product;

[0022] Step 4, filtering the filtrate after acidification in step 3 to obtain a precipitated solid product, washing it with distilled water until it is neutral, and drying it to obtain modified p-toluenesulfonic acid.

[0023] Preferably, in step 1, the weight volume ratio of p-toluenesulfonic acid to concentrated sulfuric acid and concentrated nitric acid is 5-15 g: 20-40 ml: 10-20 ml.

[0024] Preferably, in step 2, the weight volume ratio of the iron powder to anhydrous ethanol and hydrochloric acid is 15-25 g:80-120 ml:3-7 ml, and the weight ratio of the obtained nitration product to the iron powder is 10-13:15-25.

[0025] Preferably, in step 3, the weight volume ratio of potassium permanganate to distilled water is 5-10 g:120-180 ml, and the weight ratio of the obtained amination product to potassium permanganate is 1-1.2:1.

[0026] Through the modified p-toluenesulfonic acid, amino groups (-NH2) and carboxyl groups (-COOH) are introduced. Amino groups (-NH2) are highly active functional groups that can interact with other molecules through hydrogen bonds. In polyaniline, amino groups can form hydrogen bonds with dopants or other molecules through NH bonds. The formation of hydrogen bonds can enhance the binding force between the dopant and polyaniline, thereby improving the stability of the doped polyaniline. The presence of hydrogen bonds has a certain effect on the microstructure of polyaniline, changing the arrangement of the polyaniline chain and the intermolecular interaction, thereby improving its conductivity. Under certain conditions, carboxyl groups (-COOH) can dissociate hydrogen ions to form negatively charged carboxylate ions, which can form ionic interactions with the positively charged parts on the polyaniline molecular chain. In addition, the oxygen atoms in the carboxyl group can also form hydrogen bonds with hydrogen atoms on the polyaniline molecular chain. This multiple interaction enhances the binding force between the dopant and polyaniline, forms a more stable doping structure, improves the doping efficiency, and ensures the stability and durability of the conductive network. The modified p-toluenesulfonic acid makes the arrangement of the polyaniline molecular chain more regular through multiple interactions, increases the carrier concentration in the polyaniline molecular chain, forms a channel that is more conducive to charge transfer, and thus improves the conductivity of the coating. Hydrogen bonds and ionic interactions make the binding between the polyaniline molecular chains tighter and more stable, which can resist the interference of external environmental factors (such as temperature, humidity, chemicals, etc.) and improve the stability of the coating during use. The enhanced intermolecular interaction helps to improve the mechanical strength and toughness of the polyaniline coating, making it more able to withstand external mechanical stress and deformation, and reducing the possibility of cracking and damage to the coating. The stable molecular structure can better resist the erosion of corrosive media, protect the coating and substrate, and extend the service life of the polyaniline conductive coating.

[0027] Preferably, the method further comprises applying a chromium or nickel coating on the surface of the metal substrate by electroplating after the pretreatment and before the electrophoretic deposition of the conductive coating.

[0028] Electroplated chromium or nickel coatings have excellent corrosion resistance and can significantly improve the corrosion resistance of metal substrates. The anti-corrosion effect can be further enhanced by depositing polyaniline conductive coatings on these metal coatings. The polyaniline coating can form a protective layer on the metal surface through redox reactions, thereby effectively blocking the invasion of corrosive media. Chromium or nickel coatings can fill the tiny defects and pores on the surface of the metal substrate, making the surface smoother and more uniform, improving the roughness and chemical properties of the metal substrate surface, creating good conditions for the subsequent uniform deposition of polyaniline coatings, increasing the bonding force between the polyaniline conductive coatings, reducing the risk of coating delamination and peeling, and improving the stability and reliability of the coating.

[0029] The fuel cell composite metal bipolar plate obtained by the above preparation method.

[0030] A fuel cell comprises the composite metal bipolar plate mentioned above.

[0031] The present invention has the following beneficial effects:

[0032] The present invention uses an electrophoretic deposition method to deposit a conductive coating on the surface of a metal substrate. In its precursor solution, polyaniline is used as the main conductive polymer, and its molecular chain structure can provide a certain conductive path. Para-toluenesulfonic acid, as a dopant, can be inserted between the molecular chains of polyaniline, change the electronic structure of polyaniline, increase its carrier concentration, and thus improve the conductive properties of polyaniline. Multi-walled carbon nanotubes have extremely high conductivity and long-range electron transmission capabilities. They can be entangled and contacted with polyaniline in the solution to form a continuous conductive network, provide an efficient transmission channel for electrons, and significantly enhance the overall conductive properties. Reduced graphene oxide has a large specific surface area and good conductivity. It can fully contact with polyaniline, increase the conductive contact points, and further expand the conductive path. At the same time, its lamellar structure can also play a barrier and protective role, and improve the corrosion resistance of the coating. The chopped carbon fiber mainly serves to enhance the stability of the solution and the mechanical properties of the coating. During the coating formation process, the chopped carbon fibers can bridge and interweave between other components, improve the structural integrity and strength of the coating, reduce the generation of cracks and defects, and thus enhance the stability and durability of the coating. The synergistic effect of these components in the precursor solution enables the formation of a coating with excellent electrical conductivity, good corrosion resistance and mechanical strength in the subsequent processing process, meeting the performance requirements of fuel cell composite metal bipolar plates.

[0033] Furthermore, the modified p-toluenesulfonic acid is used as a dopant. Compared with the unmodified p-toluenesulfonic acid, the amino group (-NH2) and carboxyl group (-COOH) are introduced, so that the modified p-toluenesulfonic acid can form more complex interactions with the polyaniline molecular chain, including hydrogen bonds and ionic interactions. These interactions significantly enhance the binding force between the dopant and polyaniline, thereby significantly improving the conductivity, mechanical strength, corrosion resistance and other properties of the electrophoretically deposited polyaniline conductive coating, providing more reliable support for its application in fuel cells and other fields.

[0034] The present invention adopts electrophoretic deposition method to ensure that the material in the precursor solution is uniformly deposited on the surface of the metal substrate, forming a dense and uniform conductive coating. This process not only improves the conductivity and corrosion resistance of the coating, but also simplifies the preparation process and reduces production costs. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0036] The raw materials used in the following examples are all common commercial products. Polyaniline, molecular weight 726.87, Wuhan Kemik Biomedical Technology Co., Ltd.; multi-walled carbon nanotubes, diameter 10-30nm, length 1-2um, Guangzhou Hongwu Material Technology Co., Ltd.; reduced graphene oxide, model TG1600, Dongguan Kelude New Energy Technology Co., Ltd.; short-cut carbon fiber, length 5mm, manufacturer Jiangxi Shuobang New Material Technology Co., Ltd.; concentrated sulfuric acid, concentration 98%, concentrated nitric acid concentration 65%, hydrochloric acid concentration 37%.

[0037] Example 1

[0038] A method for preparing a fuel cell composite metal bipolar plate comprises the following steps:

[0039] (1) First, the metal base material is pretreated, including grinding, polishing and cleaning, to remove surface oxides and impurities;

[0040] (2) coating a nickel coating on the surface of the pretreated metal substrate using nickel sulfate by electroplating, wherein the electroplating is performed using a conventional process;

[0041] (3) depositing a conductive coating on the surface of the nickel coating in step (2) by electrophoretic deposition, wherein the specific steps of electrophoretic deposition of the conductive coating are as follows:

[0042] S1, preparation of precursor solution: 1.0g polyaniline was dissolved in 55ml N-methylpyrrolidone, stirred for 30min until completely dissolved, 0.1g modified p-toluenesulfonic acid was added as a dopant, stirring was continued for 30min, 0.04g multi-walled carbon nanotubes and 0.05g reduced graphene oxide were added, ultrasonic treatment was performed for 1h, and uniform dispersion was achieved; finally, 0.10g chopped carbon fiber was added, and ultrasonic treatment was continued for 1h, and the ultrasonic power was 400W;

[0043] S2, electrophoretic deposition: stainless steel was selected as the anode, the metal substrate as the cathode, the electrode spacing was 3 cm, and the electrophoretic deposition parameters were controlled as follows: voltage of 30 V, deposition time of 5 min, and current density of 2.5 mA / cm 2 , pour the precursor solution into the deposition tank, insert the electrode, apply voltage, and perform electrophoretic deposition on the surface of the metal substrate; after the deposition is completed, the coating substrate is cleaned with NMP (N-methylpyrrolidone) to remove undeposited particles and residues;

[0044] S3, post-treatment: drying at 80 °C for 1 h; curing at 140 °C for 3 h to improve the adhesion and mechanical strength of the coating;

[0045] (4) Punching and cutting the composite metal substrate obtained in step (3) to produce a composite metal bipolar plate.

[0046] The preparation method of the modified p-toluenesulfonic acid comprises the following steps:

[0047] Step 1, in a fume hood, slowly add 10g of p-toluenesulfonic acid to 30ml of concentrated sulfuric acid and stir evenly; under ice bath conditions, slowly drop 15ml of concentrated nitric acid, control the dropping speed, the dropping time is 30min, keep the reaction temperature at 0-5°C, and stir the reaction for 3h; after the reaction is completed, slowly pour the reaction solution into a large amount of ice water, let it stand for 40min and then filter to obtain a nitration product;

[0048] Step 2, dissolving the above nitration product in 100 ml of anhydrous ethanol, adding 20 g of iron powder and 4 ml of hydrochloric acid, heating to reflux for 4 hours, the heating temperature is 81° C., so that the nitro group is reduced to the amino group, and the weight ratio of the obtained nitration product to the iron powder is 11.5:20; after the reaction is completed, filtering to remove the remaining iron powder, and removing the ethanol by vacuum distillation to obtain the amination product;

[0049] Step 3, dissolving the above-mentioned amination product in 150 ml of distilled water and stirring evenly; slowly adding 7 g of potassium permanganate, controlling the reaction temperature at 65° C., reacting for 5.5 hours, and the weight ratio of the obtained amination product to potassium permanganate is 1.18:1. After the reaction is completed, adding sodium hydroxide solution to neutralize to a pH of 9-10, filtering to remove the precipitate, and then acidifying the filtrate with hydrochloric acid to a pH of 2-3 to precipitate the product;

[0050] Step 4, filtering the filtrate after acidification in step 3 to obtain a precipitated solid product, washing it with distilled water for multiple times until the washing liquid is neutral; drying the product in a vacuum drying oven at 60° C. to obtain modified p-toluenesulfonic acid.

[0051] Example 2

[0052] A method for preparing a fuel cell composite metal bipolar plate comprises the following steps:

[0053] (1) First, the metal base material is pretreated, including grinding, polishing and cleaning, to remove surface oxides and impurities;

[0054] (2) applying a nickel coating on the surface of the pretreated metal substrate using nickel sulfate by electroplating;

[0055] (3) depositing a conductive coating on the surface of the metal substrate by electrophoretic deposition, wherein the specific steps of electrophoretic deposition of the conductive coating are:

[0056] S1, preparation of precursor solution: 1.5g polyaniline was dissolved in 60ml N-methylpyrrolidone, stirred for 20min until completely dissolved, 0.05g modified p-toluenesulfonic acid was added as a dopant, stirring was continued for 20min, 0.03g multi-walled carbon nanotubes and 0.07g reduced graphene oxide were added, ultrasonic treatment was performed for 0.5h, and uniform dispersion was achieved; finally, 0.15g chopped carbon fiber was added, and ultrasonic treatment was continued for 1.2h, and the ultrasonic power was 350W;

[0057] S2, electrophoretic deposition: stainless steel was selected as the anode, the metal substrate as the cathode, the electrode spacing was 2 cm, and the electrophoretic deposition parameters were controlled as follows: voltage of 25 V, deposition time of 3 min, and current density of 1 mA / cm 2 , pour the precursor solution into the deposition tank, insert the electrode, apply voltage, and perform electrophoretic deposition on the surface of the metal substrate; after the deposition is completed, the coating substrate is cleaned with NMP to remove undeposited particles and residues;

[0058] S3, post-treatment: drying at 100 °C for 0.5 h; curing at 120 °C for 4 h to improve the adhesion and mechanical strength of the coating;

[0059] (4) Punching and cutting the composite metal substrate obtained in step (3) to produce a composite metal bipolar plate.

[0060] The preparation method of the modified p-toluenesulfonic acid comprises the following steps:

[0061] Step 1, in a fume hood, slowly add 5g of p-toluenesulfonic acid to 20ml of concentrated sulfuric acid and stir evenly; under ice bath conditions, slowly drop 10ml of concentrated nitric acid, control the dropping speed, drop for 45min, keep the reaction temperature at 0-5°C, and stir the reaction for 2.5h; after the reaction is completed, slowly pour the reaction solution into a large amount of ice water, let it stand for 30min, and then filter to obtain a nitration product;

[0062] Step 2, dissolving the above nitration product in 80 ml of anhydrous ethanol, adding 15 g of iron powder and 3 ml of hydrochloric acid, heating to reflux for 3 h, the heating temperature is 82° C., so that the nitro group is reduced to the amino group, and the weight ratio of the obtained nitration product to the iron powder is 10:25; after the reaction is completed, filtering to remove the remaining iron powder, and removing the ethanol by vacuum distillation to obtain an amination product;

[0063] Step 3, dissolving the above-mentioned amination product in 140 ml of distilled water and stirring evenly; slowly adding 5 g of potassium permanganate, controlling the reaction temperature at 60° C., reacting for 4 hours, and the weight ratio of the obtained amination product to potassium permanganate is 1:1. After the reaction is completed, adding sodium hydroxide solution to neutralize to a pH of 9-10, filtering to remove the precipitate, and then acidifying the filtrate with hydrochloric acid to a pH of 2-3 to precipitate the product;

[0064] Step 4, filtering the filtrate after acidification in step 3 to obtain a precipitated solid product, washing it with distilled water for multiple times until the washing liquid is neutral; drying the product in a vacuum drying oven at 65° C. to obtain modified p-toluenesulfonic acid.

[0065] Example 3

[0066] A method for preparing a fuel cell composite metal bipolar plate comprises the following steps:

[0067] (1) First, the metal base material is pretreated, including grinding, polishing and cleaning, to remove surface oxides and impurities;

[0068] (2) applying a nickel coating on the surface of the pretreated metal substrate using nickel sulfate by electroplating;

[0069] (3) depositing a conductive coating on the surface of the metal substrate by electrophoretic deposition, wherein the specific steps of electrophoretic deposition of the conductive coating are:

[0070] S1, preparation of precursor solution: 0.5g polyaniline was dissolved in 40ml N-methylpyrrolidone, stirred for 40min until completely dissolved, 0.15g modified p-toluenesulfonic acid was added as a dopant, stirring was continued for 40min, 0.07g multi-walled carbon nanotubes and 0.03g reduced graphene oxide were added, ultrasonic treatment was performed for 1.5h, and uniform dispersion was achieved; finally, 0.05g chopped carbon fiber was added, and ultrasonic treatment was continued for 0.5h, and the ultrasonic power was 450W;

[0071] S2, electrophoretic deposition: stainless steel was selected as the anode, the metal substrate as the cathode, the electrode spacing was 4 cm, and the electrophoretic deposition parameters were controlled as follows: voltage of 40 V, deposition time of 7 min, and current density of 3 mA / cm 2 , pour the precursor solution into the deposition tank, insert the electrode, apply voltage, and perform electrophoretic deposition on the surface of the metal substrate; after the deposition is completed, the coating substrate is cleaned with NMP to remove undeposited particles and residues;

[0072] S3, post-treatment: drying at 60 °C for 1.5 h; curing at 160 °C for 2 h to improve the adhesion and mechanical strength of the coating;

[0073] (4) Punching and cutting the composite metal substrate obtained in step (3) to produce a composite metal bipolar plate.

[0074] The preparation method of the modified p-toluenesulfonic acid comprises the following steps:

[0075] Step 1, in a fume hood, slowly add 15g of p-toluenesulfonic acid to 40ml of concentrated sulfuric acid and stir evenly; under ice bath conditions, slowly drop 20ml of concentrated nitric acid, control the dropping speed, the dropping time is 35min, keep the reaction temperature at 0-5°C, and stir the reaction for 3.5h; after the reaction is completed, slowly pour the reaction solution into a large amount of ice water, let it stand for 60min and then filter to obtain a nitration product;

[0076] Step 2, dissolving the above nitration product in 120 ml of anhydrous ethanol, adding 25 g of iron powder and 7 ml of hydrochloric acid, heating to reflux for 5 hours, the heating temperature is 80° C., so that the nitro group is reduced to the amino group, and the weight ratio of the obtained nitration product to the iron powder is 13:15; after the reaction is completed, filtering to remove the remaining iron powder, and removing the ethanol by vacuum distillation to obtain the amination product;

[0077] Step 3, dissolving the above-mentioned amination product in 120 ml of distilled water and stirring evenly; slowly adding 10 g of potassium permanganate, controlling the reaction temperature at 70° C., reacting for 6 hours, and the weight ratio of the obtained amination product to potassium permanganate is 1.2:1. After the reaction is completed, adding sodium hydroxide solution to neutralize to a pH of 9-10, filtering to remove the precipitate, and then acidifying the filtrate with hydrochloric acid to a pH of 2-3 to precipitate the product;

[0078] Step 4, filtering the filtrate after acidification in step 3 to obtain a precipitated solid product, washing it with distilled water for multiple times until the washing liquid is neutral; drying the product in a vacuum drying oven at 55° C. to obtain modified p-toluenesulfonic acid.

[0079] Example 4

[0080] A method for preparing a fuel cell composite metal bipolar plate comprises the following steps:

[0081] (1) First, the metal base material is pretreated, including grinding, polishing and cleaning, to remove surface oxides and impurities;

[0082] (2) applying a nickel coating on the surface of the pretreated metal substrate using nickel sulfate by electroplating;

[0083] (3) depositing a conductive coating on the surface of the metal substrate by electrophoretic deposition, wherein the specific steps of electrophoretic deposition of the conductive coating are:

[0084] S1, preparation of precursor solution: 1.2g polyaniline was dissolved in 50ml N-methylpyrrolidone, stirred for 25min until completely dissolved, 0.12g modified p-toluenesulfonic acid was added as a dopant, stirring was continued for 25min, 0.05g multi-walled carbon nanotubes and 0.04g reduced graphene oxide were added, ultrasonic treatment was performed for 0.5h, and uniform dispersion was achieved; finally, 0.12g chopped carbon fiber was added, and ultrasonic treatment was continued for 1.5h, and the ultrasonic power was 420W;

[0085] S2, electrophoretic deposition: stainless steel was selected as the anode, the metal substrate as the cathode, the electrode spacing was 2 cm, and the electrophoretic deposition parameters were controlled as follows: voltage of 20 V, deposition time of 4 min, and current density of 2 mA / cm 2 , pour the precursor solution into the deposition tank, insert the electrode, apply voltage, and perform electrophoretic deposition on the surface of the metal substrate; after the deposition is completed, the coating substrate is cleaned with NMP to remove undeposited particles and residues;

[0086] S3, post-treatment: drying at 70 °C for 1 h; curing at 130 °C for 3 h to improve the adhesion and mechanical strength of the coating;

[0087] (4) Punching and cutting the composite metal substrate obtained in step (3) to produce a composite metal bipolar plate.

[0088] The preparation method of the modified p-toluenesulfonic acid comprises the following steps:

[0089] Step 1, in a fume hood, slowly add 8g of p-toluenesulfonic acid to 32ml of concentrated sulfuric acid and stir evenly; under ice bath conditions, slowly drop 17ml of concentrated nitric acid, control the dropping speed, the dropping time is 40min, keep the reaction temperature at 0-5°C, and stir the reaction for 2.8h; after the reaction is completed, slowly pour the reaction solution into a large amount of ice water, let it stand for 50min and then filter to obtain a nitration product;

[0090] Step 2, dissolving the above nitration product in 90 ml of anhydrous ethanol, adding 18 g of iron powder and 6 ml of hydrochloric acid; heating to reflux for 4.5 hours at a heating temperature of 84° C. to reduce the nitro group to the amino group, and the weight ratio of the obtained nitration product to the iron powder is 12:18; after the reaction is completed, filtering to remove the remaining iron powder, and removing the ethanol by vacuum distillation to obtain an amination product;

[0091] Step 3, dissolving the above-mentioned amination product in 180 ml of distilled water and stirring evenly; slowly adding 9 g of potassium permanganate, controlling the reaction temperature at 63° C., reacting for 5 hours, and the weight ratio of the obtained amination product to potassium permanganate is 1.15:1; after the reaction is completed, adding sodium hydroxide solution to neutralize to a pH of 9-10, filtering to remove the precipitate, and then acidifying the filtrate with hydrochloric acid to a pH of 2-3 to precipitate the product;

[0092] Step 4, filtering the filtrate after acidification in step 3 to obtain a precipitated solid product, washing it with distilled water for multiple times until the washing liquid is neutral; drying the product in a vacuum drying oven at 70° C. to obtain modified p-toluenesulfonic acid.

[0093] Comparative Example 1

[0094] A method for preparing a fuel cell composite metal bipolar plate, wherein, in the conductive polymer, the precursor solution only contains polyaniline, and no p-toluenesulfonic acid, multi-walled carbon nanotubes, reduced graphene oxide, or chopped carbon fibers are added, and the rest is the same as in Example 1.

[0095] Comparative Example 2

[0096] A method for preparing a fuel cell composite metal bipolar plate, wherein, in the conductive polymer, p-toluenesulfonic acid is ordinary unmodified p-toluenesulfonic acid, and the rest is the same as in Example 1.

[0097] Performance Testing:

[0098] The contact resistance and corrosion current density of the bipolar plates containing the composite protective coating prepared in Examples 1-4 and Comparative Examples 1-2 were tested. The test methods were all in accordance with GB / T20042.6-2011, wherein the corrosion current density was tested by potentiodynamic polarization using an electrochemical workstation, and polarized at a constant potential (0.6 V vs. SCE) for 1 h in a 0.5M H2 SO4+1ppm HF solution at 80°C. The contact resistance and corrosion current density test results are shown in Table 1.

[0099] Table 1. Corrosion current density and contact resistance test results

[0100] project <![CDATA[Corrosion current density (μA / cm 2 , 0.6V)]]> <![CDATA[Contact resistance mΩ·cm 2 (Pressure 0.6 MPa)]]> Example 1 0.12 3.8 Example 2 0.09 3.4 Example 3 0.08 3.5 Example 4 0.13 3.7 Comparative Example 1 0.86 7.4 Comparative Example 2 0.72 7.1

[0101] It can be seen from Table 1 that the contact resistance and corrosion current density of the composite metal bipolar plates of Examples 1-4 of the present invention are lower than those of Comparative Examples 1-2, indicating that in Examples 1-4, the composite metal bipolar plates obtained by doping polyaniline with modified p-toluenesulfonic acid and adding multi-walled carbon nanotubes, reduced graphene oxide, and chopped carbon fibers for electrophoretic deposition have better conductivity and corrosion resistance than Comparative Examples 1 and 2.

[0102] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0103] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a fuel cell composite metal bipolar plate, characterized in that: Firstly, the metal substrate material is pretreated to remove surface impurities, and then a conductive coating is deposited on the surface of the metal substrate by electrophoretic deposition; The specific steps of electrophoretic deposition of the conductive coating are: S1, preparation of precursor solution: dissolving polyaniline in N-methylpyrrolidone, stirring until completely dissolved, then adding modified p-toluenesulfonic acid as a dopant, continuing stirring for 20-40 minutes, then adding multi-walled carbon nanotubes and reduced graphene oxide, performing ultrasonic treatment, after uniform dispersion, adding chopped carbon fibers, continuing ultrasonic treatment, and obtaining a precursor solution; S2, electrophoretic deposition: pour the precursor solution into the deposition tank, insert the electrode, apply voltage, and perform electrophoretic deposition on the surface of the metal substrate; S3, post-treatment: drying at 60-100°C for 0.5-1.5h, curing at 120-160°C for 2-4h.

2. The method for preparing a fuel cell composite metal bipolar plate according to claim 1, characterized in that: In step S1, the weight volume ratio of the polyaniline to N-methylpyrrolidone is 0.5-1.5 g:40-60 ml, and the weight ratio of the polyaniline to modified p-toluenesulfonic acid, multi-walled carbon nanotubes, and reduced graphene oxide is 0.5-1.5:0.05-0.15:0.03-0.07:0.03-0.

07.

3. The method for preparing a fuel cell composite metal bipolar plate according to claim 1, characterized in that: In step S2, stainless steel is used as the anode, the metal substrate is used as the cathode, and the electrode spacing is 2-4 cm; the electrophoretic deposition parameters are: voltage 20-40 V, deposition time 3-7 min, current density 1-3 mA / cm 2 .

4. The method for preparing a fuel cell composite metal bipolar plate according to claim 1, characterized in that: The preparation method of the modified p-toluenesulfonic acid comprises the following steps: Step 1, add p-toluenesulfonic acid to concentrated sulfuric acid, stir evenly, add concentrated nitric acid dropwise under ice bath conditions, the addition time is 30-45min, the reaction temperature is maintained at 0-5°C, the reaction is stirred for 2.5-3.5h, after the reaction is completed, the reaction solution is poured into ice water, allowed to stand for 30-60min and then filtered to obtain a nitration product; Step 2, dissolving the nitration product in anhydrous ethanol, adding hydrochloric acid and iron powder, heating to reflux for 3-5 hours, the heating temperature is 80-84° C., filtering to remove the iron powder, and removing the ethanol by vacuum distillation to obtain an amination product; Step 3, dissolving the above-mentioned amination product in distilled water, stirring evenly, adding potassium permanganate, the reaction temperature is 60-70°C, reacting for 4-6 hours, adding sodium hydroxide solution to neutralize to a pH of 9-10, filtering to remove the precipitate, and then acidifying the filtrate with hydrochloric acid to a pH of 2-3; Step 4, filtering the filtrate after acidification in step 3 to obtain a precipitated solid product, washing it with distilled water until it is neutral, and drying it to obtain modified p-toluenesulfonic acid.

5. The method for preparing a fuel cell composite metal bipolar plate according to claim 4, characterized in that: In step 1, the weight volume ratio of p-toluenesulfonic acid to concentrated sulfuric acid and concentrated nitric acid is 5-15 g: 20-40 ml: 10-20 ml.

6. The method for preparing a fuel cell composite metal bipolar plate according to claim 4, characterized in that: In step 2, the weight volume ratio of the iron powder to anhydrous ethanol and hydrochloric acid is 15-25 g:80-120 ml:3-7 ml, and the weight ratio of the obtained nitration product to the iron powder is 10-13:15-25.

7. The method for preparing a fuel cell composite metal bipolar plate according to claim 4, characterized in that: In step 3, the weight volume ratio of potassium permanganate to distilled water is 5-10 g:120-180 ml, and the weight ratio of the obtained amination product to potassium permanganate is 1-1.2:

1.

8. The method for preparing a fuel cell composite metal bipolar plate according to claim 1, characterized in that: The method also includes applying a chromium or nickel coating on the surface of the metal substrate by electroplating after pretreatment and before electrophoretic deposition of the conductive coating.

9. A fuel cell composite metal bipolar plate obtained by the preparation method according to any one of claims 1 to 8.

10. A fuel cell, characterized in that: Including the composite metal bipolar plate as described in claim 9.

Citation Information

Patent Citations

  • Surface treatment method for bipolar plate of fuel cell, bipolar plate and fuel cell

    CN117385313A

  • Gold plating method for metal bipolar plate of hydrogen fuel cell and fuel cell

    CN118263465A

  • Preparation method of molecular recognition sensor by electro-deposition

    CN101776635A

  • Polyaniline / metal oxide / carbon fiber composite cathode, seawater battery and preparation method of composite cathode

    CN109037663A

  • Graphene oxide / polyaniline hollow microsphere rigid-flexible structure modified carbon fiber, preparation method and composite material thereof

    CN116427177A